2013
DOI: 10.3178/hrl.7.66
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of extreme daily rainfall in the Mekong River Basin using a gridded precipitation dataset

Abstract: Abstract:The objective of this research was to evaluate the applicability of the Asian Precipitation Highly Resolved Observational Data Integration Towards Evaluation of Water Resources (APHRODITE) gridded dataset to develop a spatially distributed extreme daily rainfall map in Southeast Asia. We compared the extreme daily rainfall values of the 5-year return period, estimated by a frequency analysis based on annual maximum rainfall during 1987-2006 from the APHRODITE dataset and rainfall observations from 185… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Andermann et al [39] shown that for APHRODITE data also it can present relatively good performances in yearly and monthly steps in mountain areas of Himalaya front, and its performances in daily step is still need to be improved. Ono et al [40] also reported that for the heavy rainfall investigation in Mekong River, the local topography is still need to be considered as a correction factor for improving the accurate of APHRODITE data. The results of our research indicate that for their applications in local regions, the applicability, especially, topographic effects should be considered and discussed firstly.…”
Section: Discussionmentioning
confidence: 99%
“…Andermann et al [39] shown that for APHRODITE data also it can present relatively good performances in yearly and monthly steps in mountain areas of Himalaya front, and its performances in daily step is still need to be improved. Ono et al [40] also reported that for the heavy rainfall investigation in Mekong River, the local topography is still need to be considered as a correction factor for improving the accurate of APHRODITE data. The results of our research indicate that for their applications in local regions, the applicability, especially, topographic effects should be considered and discussed firstly.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ono el al. [47] found that extreme precipitation derived from the APHRODITE was lower than observations in Laos and Vietnam. Nevertheless, the product remains by far the most reliable precipitation product in this region since it employs a large number of rain gauges to generate precipitation estimates [29].…”
Section: Discussionmentioning
confidence: 63%
“…Such precipitation records are also discontinuous, short term, uncertain, and not even readily available mainly as a result of the various transboundary conflicts among all of the riparian countries concerning the exploitation of available freshwater resources in the LMRB (Lutz et al, 2014;Villafuerte & Matsumoto, 2015). Previous studies have already confirmed the functionality of gauge-based gridded precipitation data sets in assessing precipitation variability and changes in Southeast Asia (Sun et al, 2018;Villafuerte & Matsumoto, 2015;Yatagai et al, 2009Yatagai et al, , 2012, particularly in the LMRB (Chen et al, 2018;Lutz et al, 2014;Ono et al, 2013). Hence, this study extracted high-resolution (0.25°× 0.25°), gauge-based, gridded monthly precipitation time series over the LMRB for the period 1951-2015 from the Global Precipitation Climatology Centre (GPCC) product (Becker et al, 2013;Rudolf et al, 2009;Schneider et al, 2014).…”
Section: Data Descriptionmentioning
confidence: 99%